Single-phase five level modified neutral point clamped grid connected inverter topology with front-end chopper control of DC-link capacitor voltages - Kumar, Y. Sravan; Krishna, T. Murali; Guduri, Yesuratnam (Institute of Advanced Engineering and Science, 2024)
Conventionally, only the standalone operation of a single-phase fault tolerant-based 5-level neutral point clamped (SPFT-5L-NPC) inverter with two stiff DC sources has been explained with consideration of phase disposition pulse width modulation (PD-PWM) technique. In this topology, the bidirectional switch arrangement consists of four diodes and one IGBT switch. This arrangement inherently increases conduction losses of topology. Generally, any NPC inverter topology suffers from a DC-link capacitor voltage (DCL-CV) balancing issue. In the conventional contribution of work, authors have not discussed the front-end voltage balancing issue. This study describes the extension work of a single-phase grid connection with a modified 5L-NPC (M5L-NPC) inverter topology, taking into account the aforementioned concerns. In this topology, the simple front-end chopper circuit has been utilized to balance the DCL-CVs and to reduce conduction losses, another arrangement of bidirectional switch has been utilized. In this paper, both standalone and grid connections of M5L-NPC topology have been explained along with control of DCL-CVs. The grid-connected important objectives of active power control (APC), reactive power control (RPC), and injecting sinusoidal current with low harmonic distortion have been discussed thoroughly considering a simple control strategy.